Comparing the sensory characteristics, physical properties, and consumer acceptability of purple rice cultivars - Somthawil, Somsiri; Sriwattana, Sujinda (Food and Applied Bioscience Journal, 2017)
Sensory profiles from descriptive analysis, physical properties and consumer acceptance were used to compare qualities among purple rice growing in six different locations of cooked purple rice – Phayao, Chiang Rai, Omkoi, Doi Saket, Baantumkaw and Kantai. Results showed that the high intensity ratings for purple color and black color of Omkoi purple rice corresponded to the high for color and appearance. In contrast, the high intensity ratings for brown color and the low value of L* in Kantai purple rice resulted in a low consumer acceptance score for color. The samples with high glossiness intensity ratings, even though the differences were not significant (p≥0.05), received high acceptance scores for appearance. When comparing aroma and flavor intensity ratings with acceptance scores, high acceptance scores coincided with high intensity for purple rice odor, rice flavor and purple rice flavor. Omkoi purple rice and Doi Saket purple rice had high sweetness intensity which resulted in high overall flavor and overall acceptance. The high hardness intensity ratings from descriptive analysis of Kantai purple rice and Phayao purple rice were consistent with the high hardness values measured by texture analyzer. Considering the aftertaste of cooked purple rice, the low astringency intensity ratings of Omkoi purple rice resulted in high acceptance scores, whereas the high intensity ratings the bitterness in Chiang Rai purple rice and Kantai purple rice resulted in low acceptance scores for aftertaste. Conclusively, the highest overall acceptance scores of Omkoi purple rice corresponded to the high intensity ratings for purple and black color attributes, purple rice odor, rice flavor, purple rice flavor, sweetness, springiness and stickiness as well as the low intensity rating for astringency.